L’Italia e la fine della monarchia austro-ungarica - Scarano, Federico (Studi Politici, 2025)
When the First World War broke out, no politician in the Italian government was thinking of the dissolution of Austria-Hungary; indeed, authoritative personalities, even if a minority, such as Sidney Sonnino, the future Foreign Minister who led Italy to intervene, were in favor of entering the war alongside it. Even after the declaration of war, the Italian government reiterated, until the defeat at Caporetto, that it had no intention of dissolving Austria-Hungary or changing its internal order. After that rout, which could have led to the definitive Italian collapse, Prime Minister Vittorio Emanuele Orlando decided, at least on a propaganda level, to focus on its dissolution; he wanted to convince the Slavic and Romanian soldiers to desert; he authorized the formation of a Czechoslovakian legion to be placed alongside the Italian units. However, the Italians, with regard to Austria-Hungary, contemplated three possible policies: Sonnino’s, for a total victory, but against the dissolution of Austria-Hungary; that of Nitti, in favor of a compromise peace and major Italian sacrifices, and that of Orlando, who seemed committed to the dissolution of Austria-Hungary and the creation of new states on its ashes, but in reality kept all three options open depending on the outcome of the war.